Aplikasi Sistem Manajemen Dokumen Elektronik Berorientasi Standar Borang BAN PT - Heri Suroyo; Zaid Amin (JUST IT : Jurnal Sistem Informasi, Teknologi Informasi dan Komputer, 2017)
Maintaining the documents of an institution is an important factor for the survival of an organization. So far, documents are usually manually managed both in maintenance and storage. The Electronic Document Management System application web application can be utilized to assist in managing and maintaining all documents generated from all organizational, administrative and academic activities. The use of applications in managing and maintaining documents will have many advantages and benefits of them, the document will be easier when it will be accessed or used for various purposes. By using the application then the security of documents in terms of damage, especially physical damage can be avoided. The focus of this research is Electronic Documents Management System Application Oriented Application Standard Accreditation BAN BAN PT. Application developed web-based, the importance of Electronic Documents Management System application because BAN PT as the institution in charge of assessing the quality of the college institution will refer based on the documents that have been produced by a college. The use of BAN PT standard form as an orientation in the development of this application because access to the document quickly is needed at accreditation process both institution and study program. The method of developing a software application system using Unified Process (UP) method with constraint to Construction step from Unified Proces by using UML modeling. This research has resulted in the application Electronic Documents Management System oriented standard accreditation form BAN PT. In testing the application with 4 (four) scenarios all have been running well, so the application generated in this study has been in accordance with the needs of users.Keywords: Application development, Electronic Documents Management System, Standard Borang PT, UP and UML.